2017
DOI: 10.3748/wjg.v23.i28.5158
|View full text |Cite
|
Sign up to set email alerts
|

Single amino acid mutation of SR-BI decreases infectivity of hepatitis C virus derived from cell culture in a cell culture model

Abstract: AIMTo investigate the effect of a single amino acid mutation in human class B scavenger receptor I (SR-BI) on the infectivity of cell culture-derived hepatitis C virus (HCVcc) in SR-BI knock-down Huh7-siSR-BI cells.METHODSSite-directed mutagenesis was used to construct the SR-BI S112F mutation, and the mutation was confirmed by nucleotide sequencing. SR-BI knock-down Huh7-siSR-BI cells were transfected with SR-BI S112F, SR-BI wild type (WT) and control plasmids, and then infected with HCVpp (HCV pseudoparticle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have shown that some common SR‐BI polymorphisms are associated with differential HCV treatment outcome and viral load 41,42 . In addition, naturally occurring, but very rare SR‐BI coding mutations (specifically S112F and T175A) have reduced HCV entry function 42–44 . Despite the association between SR‐BI polymorphisms and key facets of HCV replication and biology, their potential impact on disease severity has not been defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that some common SR‐BI polymorphisms are associated with differential HCV treatment outcome and viral load 41,42 . In addition, naturally occurring, but very rare SR‐BI coding mutations (specifically S112F and T175A) have reduced HCV entry function 42–44 . Despite the association between SR‐BI polymorphisms and key facets of HCV replication and biology, their potential impact on disease severity has not been defined.…”
Section: Introductionmentioning
confidence: 99%
“… 41 , 42 In addition, naturally occurring, but very rare SR‐BI coding mutations (specifically S112F and T175A) have reduced HCV entry function. 42 , 43 , 44 Despite the association between SR‐BI polymorphisms and key facets of HCV replication and biology, their potential impact on disease severity has not been defined. To address this shortfall, we used archived DNA extracts obtained from the extensively characterized Trent HCV cohort 45 to investigate the prevalence of relatively high frequency polymorphisms in individuals with severe versus mild HCV‐induced liver disease.…”
Section: Introductionmentioning
confidence: 99%